Prioritizing Learning Topics of Coding Curriculum for Elementary Students Using the Analytic Hierarchy Process - Lim, Dongkyun; Eun Lee, Ji; Moon, Dosik; Um, Gijun (International Journal of Engineering and Technology, 2018)
As the world confronts the 4th industrial revolution era, there is a growing interest in coding education around the world to cultivate creative and convergent students who possess computational thinking and problem-solving skills. In order for coding education to be successful, the following questions are considered: 1.What should be taught first? 2. How should it be taught? This study aims to determine the priority of leaning topics in elementary school coding education. To do so, a focus group interview was conducted with four experts in the field of coding education, and 12 learning topics were identified. Based on the interview results, a questionnaire was administered to coding instructors. The Analytic Hierarchy Process (AHP) was applied to derive priorities among the learning topics. The results showed that ‘procedural problem solving’ was found as the most important unit that the elementary school coding education needs to deal with. As for the learning topics, ‘problem definition and breakdown’, ‘block coding’, ‘implementation of algorithm’, ‘understanding of algorithm’ and ‘necessity for learning coding’ were found to be the top 5 priorities. Based on these results, this study presents four suggestions to consider for coding education to be carried out more effectively.